SAT0612 The use of 18F-FDG-PET in the diagnosis of polymyalgia rheumatica (PMR) – a prospective study of 99 patients suspected of PMR. (15th June 2017) - Henckaerts, L; Gheysens, O; Vanderschueren, S; Goffin, K; Blockmans, D
Abstract : Background: Previous studies have shown that the majority of patients with polymyalgia rheumatica (PMR) have increased fluorodeoxyglucose (FDG)-uptake around the shoulders, hips and processes of the cervical and lumbar spine on positron emission tomography (PET) (1). The specificity of these findings for PMR is not known. Objectives: To determine the specificity and sensitivity of FDG-PET findings for the diagnosis of PMR. Methods: A prospective monocentric study in a tertiary care centre. All patients underwent FDG-PET scanning before treatment with glucocorticoids was started. The clinical suspicion of PMR was quantified by the treating physician on a scale from 1 to 5. FDG-uptake was scored visually in 12 articular regions (cervical spinous processes, lumbar spinous processes, left and right sternoclavicular joint, left and right ischial tuberosity, left and right greater trochanter, left and right hip and left and right shoulder) (score 0–2) and a total skeletal score was calculated reflecting the FDG-uptake in these 12 articular regions. ROC analysis was performed to determine the optimal clinical and total skeletal score for diagnosing PMR. The golden standard for a diagnosis of PMR was the judgment of an experienced clinician after at least six months of follow-up. Results: 99 consecutive patients with a possible clicinal diagnosis of PMR were included in this study. Sixty-seven patients were finally diagnosed with PMR while 32 patients got another diagnosis. A clinical score of 4 or more had a sensitivity of 67.2%, specificity of 87.5%, positive predictive value (PPV) of 91.8% and a negative predictive value (NPV) of 56.0% for the diagnosis of PMR. A total skeletal score of 16 or more had a sensitivity, specificity, PPV, NPV of respectively 85.1%, 87.5%, 93.4% and 73.7%. Conclusions: FDG-PET before starting glucocorticoid therapy improves the diagnostic accuracy compared to a clinical scoring system in patients with clinical suspicion of PMR. References: Blockmans D, De Ceuninck L, Vanderschueren S, Knockaert D, Mortelmans L, Bobbaers H. Repetitive 18-fluorodeoxyglucose positron emission tomography in isolated polymyalgia rheumatica: a prospective study in 35 patients. Rheumatology (Oxford) 2007; 46: 672–7. Disclosure of Interest: None declared